Collaborative Learning in EFL Classroom: Teachers’ Perceived Benefits and Limitations - Nurjanah, Imas Siti; Suparman, Asep; Kurnia, Ateng (Universitas PGRI Adi Buana Surabaya, 2026)
This study explores English language teachers’ perceptions of the benefits and limitations of collaborative learning in English classrooms. Using a qualitative case study design grounded in social constructivist theory, the study involved five English teachers from three senior high schools in West Java, Indonesia, selected through purposive sampling based on their experience in implementing collaborative learning. Data were collected through semi-structured interviews and analyzed using thematic analysis following Braun and Clarke’s six-phase framework. The findings show that collaborative learning is perceived as beneficial in enhancing student participation, confidence, communication skills, vocabulary development, and teamwork, while also promoting a shift toward student-centered learning where teachers act as facilitators. However, several practical limitations were identified, including unequal participation among students, dominance of certain group members, classroom management challenges such as noise and time constraints, and difficulties in assessing individual contributions in group work. Overall, the study concludes that although collaborative learning is pedagogically valuable in English language teaching, its effectiveness depends on careful instructional planning, clear task structure, effective classroom management, and appropriate assessment strategies.